Incomplete Meshing Interference and Morphology of New Tooth Profile of Double Helical Synchronous Belt - Guo Jianhua; Chu Wenya; Li Wenhua; Wang Yu (Jixie chuandong)
Comparing with straight tooth synchronous belt,the double helical synchronous belt has the characteristics of high transmission accuracy,low noise,smooth running. The wear of tooth surface is mainly caused by partial meshing interference in the process of synchronous belt transmission. In order to study the effect of partial meshing on the double helical synchronous belt tooth surface interference,by using the coordinate transformation theory,the partial meshing transmission model is established under the quasi- static condition. The model of partial meshing interference morphology is established through the research of the double helical synchronous belt partial meshing mechanism. In addition,the influence of pitch difference and spiral angle on the process of double helical synchronous belt tooth surface interference and the morphology of instantaneous interference are studied. The double helical tooth and straight tooth wear experiment and calculation results show that the double helical synchronous belt has better resistant wear and performance.